Scholarly Representations of MTA’s Interpretations of Halal and Haram Food: A Literature Review - Zuharum, Abdi Saad; Harahap, Indra (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Academic studies of Majelis Tafsir Al-Qur'an (MTA) have discussed dietary rulings, scriptural interpretation, and religious authority, but their findings remain dispersed across publications with different objects and evidentiary value. This article examines how the selected literature represents four interrelated dimensions of MTA’s theology of lawful and prohibited food: scriptural foundations, interpretive methodology, the construction of halal (lawful), haram (prohibited), and ṭayyib (wholesome or good), and religious authority. It employs a qualitative literature review of academic publications identified through Google Scholar, Scopus, Crossref, Dimensions, Garuda, and DOAJ. The sources were analyzed thematically while distinguishing studies that directly examine MTA from contextual scholarship on Qur'anic food concepts. Direct evidence represents MTA as grounding dietary classifications primarily in the Qur'an and Hadith. Other MTA-specific studies describe its approach as text-oriented while also identifying interpretive revision, limited forms of legal reasoning, institutional publications, and organizational authority. Contextual scholarship broadens the meaning of ṭayyib, but does not establish that MTA adopts all its ethical, health-related, or environmental dimensions. The review integrates the four dimensions into a bounded account of how academic literature has represented MTA’s dietary theology. Its conclusions remain limited by the small and heterogeneous body of MTA-specific food research.